Filipinas in São Paulo: South-South Migrations and Domestic Service - Ester Martins-Ribeiro (Revue Internationale des Études du Développement)
In this article, I analyze the transnational migration of Filipino women moving to São Paulo to work as domestic workers, exploring the emigration context in the Philippines, the importance of South-South migrations in the care economy, the domestic service conditions in Brazil, and finally, the individual life journeys of four Filipinas. They were interviewed in a semi-structured way for this purpose. My goal is to emphasize the numerous factors that structure such mobility and domesticity, highlighting some experiences in a specific local context concerning the social division of care work and the actor’s subjectivity. In a global context, women move and undertake life-sustaining activities, combining the global economy, affections, and their own life journeys in the home’s micro space.